PERBANDINGAN KEMAMPUAN MEMBACA CERITA RAKYAT SUMATERA SELATAN DAN CERITA PENDEK TEBITAN KOMPAS - Amalia, Falina Noor (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This research was aimed to find out the comparison of the speed of reading the folklore of South Sumatra and the short story published by Kompas. The sample in this study is the Second Semester Students of Indonesian Language and Literature Education Program, Faculty of Teacher Training and Education Tridinanti University of Palembang.  The technique of data analysis was a test technique. Quantitative data analysis technique was used to analyze the mean of reading comprehension test result. The text used is South Sumatra folklore entitled Sembesat and Sembesit, while the short story published by Kompas is written by Farizal Sikumbang entitled Penagih Hutang Bersepeda Kumbang. The procedures of data analysis consisted of  measuring the speed reading (KM), content comprehension (PI), and reading ability (KMP). The texts being tested are South Sumatran folklore and the short story published by Kompas. Based on the result of research, it was found that the reading speed of South Sumatera folklore was 161,71 kpm with the comprehension level 34,04%, while the speed of reading narrative story published by Kompas is 203,71 kpm with understanding level 62,14%. This shows that the reading speed of students in reading folklore is lower than the short story published by Kompas.Keywords— Speed Reading, Folklore, Short Stories.